THE INFLUENCE OF SERVICE QUALITY, PRICE, AND PROMOTION ON CONSUMER SATISFACTION AT AHASS ANUGERAH DISA MOTOR SIDOARJO - Bilda Istandi; Vera Firdaus; Dewi Andriani (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine the effect of service quality, price and promotion on consumer satisfaction. Method: This study uses a quantitative approach as a research method. The population of this study is all consumers of Ahass Anugerah Disa Motor Sidoarjo who service and purchase spare parts at Ahass Anugerah Disa Motor Sidoarjo. This study uses a sample of 100 people selected based on respondent criteria using a purposive random sampling technique. The data used in this study are primary data, obtained through distributing questionnaires via Google From distributed to consumers. Quantitative data analysis techniques use statistical methods to analyze the data. The statistical method used is SPSS 25. Results: Based on the results of the study, it was found that service quality has a positive and significant effect on consumer satisfaction of Ahass Anugerah Disa Motor Sidoarjo. Price has a positive and significant effect on consumer satisfaction of Ahass Anugerah Disa Motor Sidoarjo. Promotion has a positive and significant effect on consumer satisfaction of Ahass Anugerah Disa Motor Sidoarjo. Furthermore, in this context, service quality, price, and promotion were simultaneously proven to have a significant impact on customer satisfaction at Ahass Anugerah Disa Motor Sidoarjo. Novelty: This study highlights the simultaneous influence of service quality, price, and promotion on consumer satisfaction in the context of motorcycle service and spare part purchasing at Ahass Anugerah Disa Motor Sidoarjo.